Assessing the Effectiveness of Value-Laden Initiatives of the Department of Education Region 02 - Ponhagban, Richard (Studies in Technology and Education, 2025)
This research is focused on assessing the effectiveness of value-laden initiatives of the Department of Education Region 2 as a basis for an action plan towards its efficient and sustainable implementation. Specifically, it investigated the effectiveness of Projects RDELC and RDNEB in attaining their objectives, strategies/methods employed, learning resources, and administrative support. It also determined the challenges and impacts of these value-laden initiatives of DepEd Ro2 and how teachers, parents, and students view their implementation with its broader goal of fostering the holistic development of learners. A convergent parallel mixed-methods research design was used to investigate the study. The participants were randomly selected across the nine Schools Division Offices of DepEd Region 2. Through comprehensive analysis of both quantitative data and qualitative results, the research has illuminated the significant impact these projects have on students. The findings unequivocally demonstrate that there is a meaningful improvement in students' character development. Quantitative analysis, supported by interviews with teachers, parents, and students, has confirmed that these projects are effective value-laden initiatives within DepEd R02, significantly contributing to students' behavioral and moral development. The study’s findings advocate for the continued support and expansion of such projects, emphasizing the importance of values in achieving educational excellence. It is recommended that future research explores the long-term impact of these projects on students' lives, further contributing to the field of values education and the broader educational landscape.